Supervision Individual Conferences Through A Reality Approach to Increasing Educator Achievement Motivation - Ilhamuddin, Muhammad Farid; Saksono, ⁠Lutfi; Rifqi, Ainur; Hidaayatullaah, Hasan Nuurul (Studies in Philosophy of Science and Education, 2024)
One way that can be done to improve the quality of teachers is to carry out supervision properly. Supervision is not only carried out to improve teacher abilities, but also to increase teacher motivation, especially achievement motivation. This study aims to reveal supervision carried out through a reality approach to increase teacher achievement motivation. To achieve the research objectives, the research approach used is qualitative, with data analysis through condensation, data display, and verification / conclusion. Data collection is done through interviews, observations, and document studies. Based on the results of the research obtained, the implementation of supervision through a reality approach is carried out through three stages, namely pre-conference, conference, and post-conference. At the pre-conference stage, the supervisor together with the supervise analyze the problems experienced and agree on the time for the implementation of supervision. The Conference stage is carried out by talking personally to increase teacher motivation. At the conference stage, the reality approach is used using WDEP (Wants, Direction, Evaluation, and Planning) techniques. At the Post Conference stage, follow up on the results of the supervision carried out.